The Incarnate Lord : A Study in Thomistic Christology - White, Thomas Joseph, 1971- (Book collections on Project MUSE., 2015)
The Incarnate Lord considers central themes in Christology from a metaphysical perspective. Particular attention is given to the hypostatic union, the two natures of Christ, the knowledge and obedience of Jesus, the passion and death of Christ, his descent into hell, and resurrection. A central concern of the book is to argue for the perennial importance of ontological principles of Christology inherited from patristic and scholastic authors. However, the book also seeks to advance an interpretation of Thomistic Christology in a modern context. The teaching of Aquinas is central to the study, but it is placed in conversation with various modern theologians, such as Karl Barth, Karl Rahner and Hans Urs von Balthasar. Ultimately the goal of the work is to suggest how traditional Catholic theology might thrive under modern conditions, and also develop fruitfully from engaging in contemporary controversies.